Exploring the underutilized novel foods and starches for formulation of low glycemic therapeutic foods: a review - Dega, Vijayalakshmi; Barbhai, Mrunal Deepak (Frontiers in Nutrition, 2023)
Rising incidences of life-style disorders like obesity, diabetes and cardiovascular diseases are a matter of concern coupled with escalated consumption of highly refined and high energy foods with low nutrient density. Food choices of consumers have witnessed significant changes globally with rising preference to highly processed palatable foods. Thus, it calls food scientists, researchers and nutritionists’ attention towards developing and promoting pleasant-tasting yet healthy foods with added nutritional benefits. This review highlights selected underutilized and novel ingredients from different food sources and their by-products that are gaining popularity because of their nutrient density, that can be employed to improve the nutritional quality of conventionally available empty-calorie foods. It also emphasizes on the therapeutic benefits of foods developed from these understudied grains, nuts, processing by-products of grains, fruits- and vegetable- byproducts and nutraceutical starches. This review aims to draw attention of food scientists and industrialists towards popularizing the utilization of these unconventional, yet nutrient rich foods sources in improving the nutritional profile of the conventional foods lacking in nutrient density